Does Company Size Moderate the Effect of Intangible Assets on Its Value? (A Case Study of Chemical Companies Listed on the IDX) - Martinus Robert Hutauruk (Облік і фінанси, 2024)
The main goal of a company is to maximize profits for its shareholders, which is realized in the form of efforts to increase the market value of the company's share price in question. In scientific and technical progress conditions, the ownership of intangible assets can significantly increase the company's capitalization and the market value of its shares. This research aims to analyze the influence of intangible assets on company value moderated by company size with the control variables of leverage and profitability. The sample of this study is 108 chemical sub-sector companies listed in the Indonesia Stock Exchange (IDX) from 2013 to 2022. The study employed quantitative data obtained from secondary sources, including companies' yearly financial statements, the Indonesian Capital Market Directory (ICMD), and the official website of IDX (www.idx.co.id). The model and analysis technique uses Moderation Regression Analysis (MRA) with linear regression-process (Andrew Hayes) and IBM SPSS. The research found that intangible assets and size partially had a positive and significant effect on company value, as did leverage and profitability as control factors. However, on the other hand, size moderation weakens the relationship between intangible assets and company value. This situation shows that not all chemical subsector companies on the IDX align with the book value of shares and the share market price. Apart from that, the proportion of assets to liabilities must also be increased to build investor and public perceptions regarding the reliability of chemical companies' intangible assets in the future. It is hoped that company size will increasingly become a factor that strengthens the creation of company value in the future. Thus, companies with greater total assets, particularly intangible assets, will provide confidence in the company's financial capabilities to investors and other parties, especially those who provide sources of capital.